2019
DOI: 10.1080/15592294.2019.1644878
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro attempt at precision toxicology reveals the involvement of DNA methylation alteration in ochratoxin A-induced G0/G1 phase arrest

Abstract: Precision toxicology evaluates the toxicity of certain substances by isolating a small group of cells with a typical phenotype of interest followed by a single cell sequencing-based analysis. In this in vitro attempt, ochratoxin A (OTA), a typical mycotoxin and food contaminant, is found to induce G0/G1 phase cell cycle arrest in human renal proximal tubular HKC cells at a concentration of 20 μM after a 24h-treatment. A small number of G0/G1 phase HKC cells are evaluated in both the presence and absence of OTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 64 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…Fluorescence analysis of DNMT1 showed alterations in global DNA methylation, thus correlating OTA-nephrotoxicity with epigenetic changes. The genome-wide hypermethylation may contribute to OTAmediated the inhibition of cell cycle progression (Zhang et al, 2020).…”
Section: Gastrointestinal Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence analysis of DNMT1 showed alterations in global DNA methylation, thus correlating OTA-nephrotoxicity with epigenetic changes. The genome-wide hypermethylation may contribute to OTAmediated the inhibition of cell cycle progression (Zhang et al, 2020).…”
Section: Gastrointestinal Toxicitymentioning
confidence: 99%
“…In the same in vitro model, OTA may exert deleterious effects by inducing DNA damage, disrupting DNA repair-related processes and arresting the cell cycle at phase G 2 /M. DNA damage was detected by the over-expression of DSB gene, γ-H2AX, and DNA repair-related genes, BRCA1 and RAD51 (Zhang et al, 2020).…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Zhang B et al showed an OTA-induced cell cycle G0/G1 phase arrest in human proximal tubular cells via DNA methylation alteration [33]. Current evidence suggests that cell cycle arrest is a hallmark of senescence induced by ROS production in renal tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon could be attenuated by NAC, suggesting that OTA induced ER-stress-mediated apoptosis through ROS-dependent pathways. Zhang B et al showed an OTA-induced cell cycle G0/G1 phase arrest in human proximal tubular cells via DNA methylation alteration [33]. Current evidence suggests that cell cycle arrest is a hallmark of senescence induced by ROS production in renal tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the gene was related to G0/G1 cell cycle arrest, but only increased expression of PTEN due to OTA-induced hypomethylation of PTEN which involved in G1/S phase transition. G0/G1 phase cell cycle arrest and inhibition of the Notch and Ras/MAPK/CREB signaling pathway after OTA exposure would lead to renal toxicity [ 58 ].…”
Section: The Mechanisms Underlying Ota Nephrotoxicitymentioning
confidence: 99%